Simulation of water purification machine for vending cyber physical systems - Salo, Andrii (Technology audit and production reserves, 2017)
The object of research is a water purification machine for self-service systems. The need for purified water is at the self-service washers, coffee vending machines, and water wending machines. As a rule, such systems are located in geographically scattered places. One of the most problematic places is the selection of the correct configuration of the machine to the location. Another problematic place is high maintenance costs. Most of the existing water purification machines, which are produced today, do not have a monitoring system in their composition, results in an inefficient operation of the service department. These problems lead to a decrease in the number of users of self-service systems. To solve these problems, it is proposed to design a water purification machine that will operate as part of a 5-level vending cyber-physical system. The structure and operating principles of the water purification machine based on the reverse osmosis membrane are described. In the course of the study, Monte Carlo simulation methods were used, which allowed to select the configuration parameters of the machine in accordance with the users' requests. Critical parameters of the equipment influencing the performance of the water purification machine are determined. Based on the simulation results, two typical configurations of the TW30-1812-100 and XLE4040 membrane-based machine are selected. In addition, the software model of the water purification machine is integrated into the analytical system, which generates recommendatory solutions for the service department. The analytical system recommends not only the current replacement of functional units (filters, membranes), but also is able to predict the need for changing the configuration of the machine. This approach allows to optimize service routes and increase the efficiency of the service.